limx→π/6 3sin⁡x−3cos⁡x6x−π equals

limxπ/63sinx3cosx6xπ equals

  1. A

    3

  2. B

    13

  3. C

    3

  4. D

    13

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have,

    limxπ/63sinx3cosx6xπ=limxπ/62332sinx12cosx6xπ6=limxπ/613sinxπ6xπ6=13

    ALITER We have,

    limxπ/63sinx3cosx6xπ 00 form 

    =limxπ/63cosx+3sinx6               [Using De L Hospital's Rule] 

    =163cosπ6+3sinπ6=13

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.